The effect of the team games tournament model with the traditional game media to train critical thinking ability in elementary school students - Suriya Ningsyih; Hairunisa Hairunisa; Nunung Fatimah; Mariani Ulfa (Jurnal Pijar Mipa, 2022)
This study aims to determine the effect of the team games tournament (TGT) learning model with the coglak media of areca nut as a traditional game to train the critical thinking skills of the fifth-grade school students in science learning. This research is quantitative research. The one group pretest-posttest design was applied in this study. The sample in this study were the fifth-grade students at SDN Imppres Mawu in academic year 2020/2021. The instrument used is a test using essay questions adapted to critical thinking indicatorsÃ¢â¬âdata analysis using technical analysis of N-Gain test data. N-Gain test is used to calculate students' critical thinking skills. Training students' critical thinking skills obtained an average N-Gain value of 0.32 with a medium category level. In conclusion, there is an influence on the team's games tournament model with the coglak media of areca nut as a traditional game to train students' critical thinking skills to be applied to help train students' critical thinking skills.